All Days 1984
DOI: 10.2118/12652-ms
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Viscoelastic Effects of Polyacrylamide Solutions

Abstract: This paper was presented at the SPE/DOE Fourth Symposium on Enhanced Oil Recovery held in Tulsa, OK, April 15-18, 1984. The material is subject to correction by the author. Permission to copy is restricted to an abstract of not more than 300 words. Write SPE, 6200 North Central Expressway, Drawer 64706, Dallas, Texas 75206 USA. Telex 730989 SPEDAL. Al:ISTRACTBeyond a critical rate of flow in cores the viscoelasticity of polyacrylamide solutions is reflected by shear thickening behaviour. Practical information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 14 publications
(1 reference statement)
5
38
0
Order By: Relevance
“…9). This behavior has been consistently reported by experimentalists in the literature for the past 40 years (Jennings et al 1971;Maerker 1975;Heemskerk et al 1984;Seright 1991b;Seright et al 2011). Oddly, a misconception persists that HPAM solutions show only Newtonian or shear-thinning behavior in porous media-not shear thickening (Lake 1989).…”
Section: Rheology In Porous Media Mechanical Degradation and Injectsupporting
confidence: 83%
See 1 more Smart Citation
“…9). This behavior has been consistently reported by experimentalists in the literature for the past 40 years (Jennings et al 1971;Maerker 1975;Heemskerk et al 1984;Seright 1991b;Seright et al 2011). Oddly, a misconception persists that HPAM solutions show only Newtonian or shear-thinning behavior in porous media-not shear thickening (Lake 1989).…”
Section: Rheology In Porous Media Mechanical Degradation and Injectsupporting
confidence: 83%
“…Shear thickening in porous media has been attributed to increased stresses and energy expenditure associated with disentanglement and elongation of coiled HPAM molecules as they flow through the sequentially contracting/dilating flow paths within porous media. Previous studies of this shear-thickening behavior in porous media focused on solutions with salinities ranging from 3,000 ppm to 50,000 ppm TDS (Jennings et al 1971;Maerker 1975;Heemskerk et al 1984;Seright 1991b;Seright et al 2011). Our study extends conditions in which this behavior has been observed down to only 500 ppm TDS.…”
Section: Rheology In Porous Media Mechanical Degradation and Injectmentioning
confidence: 99%
“…2 of Seright (1991)]. The low-viscosity shear-thickening fl uid in Table 4 was based on a 1-million-dalton HPAM and a Heemskerk model (Heemskerk 1984) that provided resistance factors of ≈7 at low fl ux and 20 at 1,000 ft/D. The high-viscosity shear-thickening fl uid was based on a 26-million-dalton HPAM and a Heemskerk model that provided resistance factors of ≈100 at low fl ux and 1,000 at 100 ft/D [ Fig.…”
Section: Impact Of Rheologymentioning
confidence: 99%
“…The experimental data were fitted to the classic Rouse model. 13 In this model, the polymer molecule is represented as a flexible chain of N beads connected by N-1 elastic springs. When immersed in a solvent fluid, such a model molecule has N-1 relaxation times which are related to the storage and loss moduli as follows:…”
Section: Rheological Measurementsmentioning
confidence: 99%